A novel medium-temperature form-stable phase change material based on dicarboxylic acid eutectic mixture/expanded graphite composites. (February 2017) - Liu, Shang; Han, Lipeng; Xie, Shaolei; Jia, Yongzhong; Sun, Jinhe; Jing, Yan; Zhang, Quanyou
Highlights: A novel PCM based on dicarboxylic acid and expanded graphite was presented. The stability and reliability were promoted in succinic acid/adipic acid eutectics. The leakage of acid was alleviated by incorporating corresponding acid into EG. The feasibility of succinic acid as a phase change material was verified. Abstract: Low stability, reliability, and corrosion are considerable challenges to widespread application of succinic acid (SA) as phase change material (PCM). Here, we present a novel medium-temperature form-stable phase change material (FSPCM) aiming to eliminate these obstacles. In this study, FSPCM was fabricated by adsorbing eutectics of adipic acid (AA) and SA into expanded graphite (EG). The molar ratio of AA and SA in eutectics was determined to be 7:3, and the optimal mass ratio of EG in FSPCM is ca. 0.1. The composite was characterized by diffraction scanning calorimetry, scanning electron microscopy, Fourier transform infrared spectrometer, X-ray diffractometer, and thermal gravimetric analyzer. The results showed that the FSPCM melts at ca. 135 °C with latent heat storage of 206 J/g. No notable change of thermal behavior in FSPCM was observed after experienced 100 accelerated cycle test. Compared to SA, both the stability and reliability were promoted in FSPCM. Besides, the leakage of dicarboxylic acid was prevented, thus the corrosion was alleviated. It is envisioned that the as-prepared FSPCM have considerable potential in medium-temperature latent heat storage.